Lessons learned: Telemedicine patterns and clinical application in patients with gynecologic cancers during COVID-19 - Sarah A. Ackroyd; Melinique Walls; Josephine S. Kim; Nita K. Lee (Elsevier, 2022)
Objective: To describe the use of telemedicine in gynecologic oncology and identify patient characteristics associated with telemedicine use during COVID-19. Methods: Single-institution retrospective chart review of patients with gynecologic cancer who participated in in-person and telemedicine visits (video and telephone) from January 2019 to November 2020. Patient characteristics, visit and treatment characteristics were collected. Comparisons between 2019 and 2020 and between in-person and telemedicine visits were performed. Cancer-specific visit details were described. Results: From January to November 2020, 2,039 patients attended 5240 ambulatory visits in our gynecologic oncology outpatient clinics with 4,304 (82.1%) in-person visits, 512 (9.8%) video telemedicine visits, and 424 (8.1%) telephone visits. In 2020, 936 (45.9%) patients participated in a telemedicine visit. Demographic characteristics did not differ between those who participated in any telemedicine versus in-person visits (p > 0.05). Black patients represented a larger share of telephone visits but this was not significant. Patients aged > 65 years were more likely to use the telephone for a visit and less likely to use video visits compared to their younger counterparts. The majority of patients who attended a telemedicine visit also attended a visit in-person (88.0%). The most common purpose of the telemedicine visits was to discuss results and/or treatment plans (46%) with other appointments occurring for treatment check-ins and clinical trials. Conclusions: The use of telemedicine drastically increased in 2020. Patient demographics were not different between in-person and telemedicine visits except that older patients were more likely to use telephone visits over video visits. Telemedicine can be used for a variety of care needs in gynecologic oncology but further work needs to be done to optimize implementation, assess cost-effectiveness and patient outcomes.